Pengembangan Bahan Ajar Berbasis Masalah Terintegrasi Etnomatematika Untuk Meningkatkan Kemampuan Pemecahan Masalah Siswa Kelas XI SMA - Ana Wiska; Henra Saputra Tanjung; Arief Aulia Rahman; Cut Eva Nasryah (Edunesia: Jurnal Ilmiah Pendidikan, 2020)
Abstract: It takes teaching material that can train students in solving mathematical problems. One of the teaching materials that can be developed to improve students' mathematical problem solving skills is problem-based teaching material. The purpose of this research is to describe: the validity of integrated problem-based ethnomatematics teaching materials developed; the effectiveness of ethnomatematics integrated problem-based teaching materials developed; and student responses to integrated problem-based ethnomatematics teaching materials developed. This research is a research development. This research was conducted through two stages, namely the first stage of developing ethnomatematics integrated problem-based teaching materials using the Four-D model, and the second stage of testing the ethnomatematics integrated problem-based teaching materials developed in class XI of SMA Negeri 1 Meureubo to see their effectiveness. From these two stages, it was obtained: integrated ethnomatemics problem-based teaching materials developed were valid, based on the results of the validation conducted by the validators; integrated ethnomatematics problem-based teaching materials developed effectively, in terms of classical student mastery learning and achievement of learning objectives; and positive student responses to the integrated problem-based ethnomatematics activity and teaching material developed. Abstrak: Dibutuhkan bahan ajar yang dapat melatih siswa dalam memecahkan masalah matematika. Salah satu bahan ajar yang dapat dikembangkan untuk meningkatkan kemampuan pemecahan masalah matematika siswa adalah bahan ajar berbasis masalah. Tujuan penelitian ini adalah untuk mendeskripsikan: kevalidan bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan; efektifitas bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan; dan respon siswa terhadap bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan. Penelitian ini merupakan penelitian pengembangan. Penelitian ini dilakukan melalui dua tahap, yaitu tahap pertama mengembangkan bahan ajar berbasis masalah terintegrasi etnomatematika menggunakan model pengembangan Four-D, dan tahap kedua mengujicobakan bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan di kelas XI SMA Negeri 1 Meureubo untuk melihat efektifitasnya. Dari kedua tahap tersebut, diperoleh:  bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan valid, berdasarkan hasil validasi yang dilakukan oleh para validator; bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan efektif, ditinjau dari ketuntasan belajar siswa secara klasikal serta ketercapaian tujuan pembelajaran;  dan respon positif siswa terhadap aktifitas dan bahan ajar berbasis masalah terintegrasi etnomatematika yang dikembangkan.